2021
DOI: 10.1038/s41598-021-01001-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coffee brewing methods on the chromatographic and spectroscopic profiles, antioxidant and sensory properties

Abstract: Cold brewing coffee has gained increasing popularity as a novel brewing method. A completely different flavour profile during cold brewing extraction (smooth and mild) is a result of the low-energy process, prolonged water-grind contact times and long preparation time. The aim of our research was to compare coffee drinks obtained with an innovative device for a faster, dynamic cold coffee extraction process (Hardtank) to drinks prepared traditionally in 24 h and hot brewed drinks. This study investigated the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Moreover, another application of metabolomic fingerprinting in coffee analysis included phenolic compounds and alkaloid analysis in Indonesian arabica and robusta coffee extracts based on FTIR. The study assigned bands at 1280 and 1605 cm −1 for chlorogenic acids and 3123, 3011, 1703 and 1653 cm −1 for caffeine [ 54 ].…”
Section: Metabolomics Applications In Coffee Roastingmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, another application of metabolomic fingerprinting in coffee analysis included phenolic compounds and alkaloid analysis in Indonesian arabica and robusta coffee extracts based on FTIR. The study assigned bands at 1280 and 1605 cm −1 for chlorogenic acids and 3123, 3011, 1703 and 1653 cm −1 for caffeine [ 54 ].…”
Section: Metabolomics Applications In Coffee Roastingmentioning
confidence: 99%
“…Coffee brewing is a historical coffee preparation method employed using various extraction methods, including drip, French press, boiled brew, pressurized extraction (espresso), and others [ 54 , 55 ]. These forms can be performed by different devices ranging from traditional brewing pots to automatized coffee makers resulting in various coffee beverages according to several factors, mainly related to consumers’ preferences and acceptability for each region or country [ 56 , 57 , 58 ].…”
Section: Metabolomics Applications In Coffee Brewingmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of previous studies have demonstrated that the roast level largely influences the composition of flavor compounds in the bean and therefore greatly impacts the final quality of the coffee drink ( Baggenstoss et al, 2008 ). Apart from the degree of roasting, coffee sensory properties are also influenced by the brewing method, and many environmental factors, such as geographical origins, climate, altitude and temperature elevation, and shading, and nutrient availability or fertilizers also have effects on the coffee sensory profile ( Stanek et al, 2021 ; Sunarharum et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%